An attention‐driven videogame based on steady‐state motion visual evoked potentials. Issue 4 (19th February 2021) - Perez‐Valero, Eduardo; Lopez‐Gordo, Miguel Angel; Vaquero‐Blasco, Miguel A.
Abstract: In Neuroscience, steady‐state visually evoked potentials (SSVEPs) have been generally used for the characterization of dynamic visual processes along the afferent pathway. In Neuroengineering, SSVEP‐based brain‐computer interfaces (SSVEP‐BCI) have been used in applications such as communications or entertainment for the detection of the overt attention to static‐flickering stimuli or other structured stimulation that involves motion (SSMVEP‐BCI). In this work, we propose an attention‐driven videogame controlled by an SSVEP‐BCI with mobile‐flickering stimuli. In this game, enemy avatars launch attacks that are presented as mobile ring‐shaped checkerboards that flicker at 15 Hz to the player, who must deflect them by exerting attention. We detected the attention of the participants based on the power spectral density of the elicited SSVEP and the adjacent electroencephalographic background noise. Twenty volunteers participated in this study. After completion, according to a game experience survey, the participants described the game as amusing and challenging. We also conducted a level survey that revealed a significant difference between the levels of attention exerted by the participants when they passed the levels with respect to when they missed ( p ‐value = 17 · 10 −5 ). Additionally, the detection accuracy of the SSVEP‐BCI had a baseline level of 84%. The results suggest that mobile flickers can be robustly detected within few seconds by means of an SSVEP‐BCI. This principle could be used as a serious game to play or train the attention and the visual tracking capabilities to mobile target stimuli in special needs education schools or in centres dealing with attention disorders.